Uso do etodolaco preemptivo na redução de sensibilidade relacionada ao clareamento dental : estudo clínico randomizado controlado triplo cego - Vaez, Savil Costa (2015)
This study evaluated the previous use of Etodolac 400 mg at the tooth sensitivity caused by bleaching procedure. This clinical randomized controlled triple blinded study was done in fifty patients, divided into two groups: Etodolac (intervention) and Placebo (control). One hour before each session, the patients received one different treatment of the first one (crossover). The treatment sequence was randomized previously of the research beginning. A anxiety questionary was applied (Corah scale), and the initial sensitivity evaluation was made by using visual and verbal scales. The bleaching procedure used 35% hydrogen peroxide (Whiteness HP Blue, FGM, Joinvile, SC, Brasil) for 40 minutes in two sessions, with 7 days interval. The sensitivity was measured before, during (20’ and 40’) and 24 hours after the dental bleaching. Color alteration was measured with CieLab system (Easy Shade Spectrophotometer) and Vita Bleach Guide scale in different periods: initial and 7 days after each dental bleaching session. Data for whitening scale were analyzed considering the scoring averages observed at baseline and after each session; and the differences (delta) between two consecutive measurements. The effect of bleaching (delta) obtained between the treatment sequences were compared using the Mann-Whitney test. Differences on presence/ absence of sensitivity were analyzed by Fisher's exact test, and the scales of assessment of tooth sensitivity, the Mann-Whitney test. For both scales of assessment of tooth sensitivity, data from scores in each moment of evaluation / whitening session, were submitted to Mann-Whitney test. The mean scores for each treatment were compared using the Wilcoxon test. The results showed that only using EVA at the second session there was some statistically significant difference, however, it was not possible to eliminate or decrease the sensitivity between treatments in the evaluated times. There was an effective bleaching for both groups, with a variation from 8.4 to 3.7 when using Bleach Guide, and 9.5 to 10.1 for the Easy Shade. The Risk and sensitivity level during and post office bleaching, in general, have not been eliminated with the preemptive use of Etodolac the bleaching procedure.